Novel Role of Red Wine-Derived Polyphenols in the Prevention of Alzheimerʼs Disease Dementia and Brain Pathology: Experimental Approaches and Clinical Implications - Pasinetti, Giulio Maria (Planta Medica, 2012)
Recent studies suggest that by the middle of this century, as many as 14 million Americans will have Alzheimerʼs disease, creating an enormous strain on families, the health care system and the federal budget. There are still widespread misconceptions about issues related to the prevention and/or treatment of disease pathogenesis, leaving us unprepared to deal with the disease. To address these challenges, several therapeutic approaches are currently under investigation, mainly in an attempt to delay disease onset and eventually slow down its progression. Recent epidemiological evidence has implicated the protective role of dietary polyphenols from grape products against Alzheimerʼs disease. Furthermore, experimental evidence supports the hypothesis that certain bioactive grape-derived polyphenols may protect against Alzheimerʼs disease-type cognitive deterioration, in part by interfering with the generation and assembly of β-amyloid peptides into neurotoxic oligomeric aggregated species. Brain-targeting polyphenols have been shown to significantly reduce the generation of β-amyloid peptides in primary cortico-hippocampal neuron cultures, and preliminary results indicate that they may influence neuronal synaptic plasticity. Recent evidence has also implicated the role of certain grape-derived preparations in beneficially modulating tau neuropathology, including reducing tau aggregation. Studies suggest that dietary polyphenolics may benefit Alzheimerʼs disease by modulating multiple disease-modifying modalities, both β-amyloid-dependent and independent mechanisms, and provide impetus for the development of polyphenolic compounds for Alzheimerʼs disease prevention and/or therapy.
Keywords: polyphenols; grape; Alzheimerʼs disease; Vitis rotundifolia; Vitaceae